PENERAPAN MODEL PROBLEM BASED LEARNING MELALUI APLIKASI QUIZIZZ UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR - Naja, Safinatun; Pratiwi, Ika Ari; Fakhriyah, Fina (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The purpose of the study was to analyze conceptual understanding in the application of the Problem Based Learning learning model using the Quizizz PKN Lesson application at SDN Tedunan.The research method used was a qualitative approach with a type of classroom action research carried out in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The study was conducted from November 2023 to May 2024 in class IV of Tedunan State Elementary School, Wedung District, Demak Regency. The subjects of the study were teachers and 15 students. Data validation with experts by filling out score sheets on each aspect related to the study. Data analysis used descriptive analysis techniques by determining the mean or average.The results of the study showed that: (1) Concept understanding in cycle I showed the acquisition of 4 students with T/High criteria, 6 students with S/Medium criteria, and the remaining 5 students with R/Low criteria. There was an increase in cycle II with the acquisition of 5 students with T/High criteria, 7 students with S/Medium criteria, and the remaining 3 students with R/Low criteria. (2) Student learning outcomes in cycle I were 10 students who experienced learning completion with a percentage of 66.70% increasing to 12 students with a percentage of 80.00% in cycle II. (3) Teacher skills in cycle I obtained a percentage of 62.50% with a total score of 20 good criteria increasing to a total score of 27 very good criteria with a percentage of 84.37% in cycle II.